Democratic Parenting Strategy From An Islamic Education Perspective: An Analysis Of Practices At At-Tajdid Senior High School Tasikmalaya - Saridudin, Saridudin (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This study aims to analyze democratic parenting strategies from an Islamic educational perspective implemented at At-Tajdid Boarding School, Tasikmalaya. The background of this research is the importance of parenting patterns that not only foster obedience but also foster independence, responsibility, and a holistic awareness of Islamic educational values. This study used a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The results indicate that democratic parenting at At-Tajdid Boarding School, Tasikmalaya, is implemented through three main strategies: open dialogue between caregivers, teachers, and students; giving students responsibility within the boarding and school environments; and fostering the internalization of Islamic educational values through role models and strengthening spiritual aspects. This strategy has successfully created a religious, participatory, and humanistic educational culture. These findings reinforce the view that democratic parenting in Islamic education not only fosters discipline but also strengthens students' character and leadership holistically.